CAFE: A Configurable pAcket Forwarding Engine for Data Center Networks - Lu, Guohan; Shi, Yunfeng; Guo, Chuanxiong; Zhang, Yongguang (ACM SIGCOMM PRESTO Workshop, 2009)
Recently, Data Center Networking (DCN) has attracted many research attentions and innovative DCN designs have been proposed . All these designs need specialized packet forwarding engines due to their special routing algorithms, which are either based on commonly used packet headers or self-defined ones. Although programmable forwarding devices are available, it is difficult to use them to prototype these DCN designs, especially when self-defined headers are introduced. In this paper, we present a hardware based Configurable pAcket Forwarding Engine (CAFE) to facilitate the prototyping process. Through simple APIs, CAFE can be easily configured to forward self-defined packets, modify, insert, and delete arbitrary packet header fields without re-designing the hardware. We have implemented CAFE using NetFPGA. Evaluation demonstrates that CAFE can be easily configured and it can forward packets at line-rate.